Maximum flow trees in overlay multicast: Modeling and optimization - Kucharzak, M.; Walkowiak, K. (2012 2nd Baltic Congress on Future Internet Communications, 2012)
Recently, peer-to-peer (P2P) multicast has become more and more popular approach of simultaneous content delivery to a group of users. It is especially valuable for multimedia applications realized in the Internet. Apart from network-based IP multicast, P2P multicast forms an overlay structure of routing where end-hosts actively contribute to the network by sharing their data streams across other receivers. The overlay structure is routed then via IP network using well-defined unicast flows. This paper focuses on modeling and optimization of content routing in overlay multicast systems. Having a set of overlay nodes interested in joining the same, single source multicast transmission, where every node is subject to limited upload and download access link capacity, we aim at providing an optimal overlay multicast in order to maximize the total system throughput and we formulate maximum flow trees problem related to multicast in overlay network. We also present an original Greedy Algorithm and Golden Ratio Heuristic for solving the problem. These algorithms are evaluated in relation to optimal results yielded by CPLEX solver and random benchmarks.